2006
DOI: 10.1038/sj.jid.5700236
|View full text |Cite
|
Sign up to set email alerts
|

Topical Application of a Novel, Hydrophilic γ-Tocopherol Derivative Reduces Photo-Inflammation in Mice Skin

Abstract: We previously demonstrated that a novel hydrophilic gamma-tocopherol (gamma-Toc) derivative, gamma-tocopherol-N,N-dimethylglycinate hydrochloride (gamma-TDMG) converts to gamma-Toc in the mouse skin and has a higher bioavailability than gamma-Toc itself. In the present study, we determined whether gamma-TDMG could reduce photo-inflammation in mouse skin, and compared its effectiveness to that of alpha-Toc acetate (alpha-TA). Topical pre- or post-application of 5% gamma-TDMG significantly reduced the formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 44 publications
2
32
0
Order By: Relevance
“…A number of studies have documented the positive effects of vitamin E, either as a stand-alone or as a part of combinatorial treatment, in reversal of oxidative stress or aging in various cellular models (Rahman et al, 2008;Ricciarelli et al, 1999;Yoshida et al, 2006). Potential application of a topical antioxidant product that included 1.0% alphatocopherol (vitamin E), among other components, was seen to activate the Nrf2 pathway and to improve skin's ability to counteract extrinsic and intrinsic insults.…”
Section: Discussionmentioning
confidence: 95%
“…A number of studies have documented the positive effects of vitamin E, either as a stand-alone or as a part of combinatorial treatment, in reversal of oxidative stress or aging in various cellular models (Rahman et al, 2008;Ricciarelli et al, 1999;Yoshida et al, 2006). Potential application of a topical antioxidant product that included 1.0% alphatocopherol (vitamin E), among other components, was seen to activate the Nrf2 pathway and to improve skin's ability to counteract extrinsic and intrinsic insults.…”
Section: Discussionmentioning
confidence: 95%
“…However, UVB doses used in previous studies are considerably higher than that of human exposure. Recent studies also indicate a link between iNOS and COX-2 expression (36). A study using a single exposure of physiologic dose of UVB to cultured human keratinocytes has shown up-regulation of COX-2 expression (11).…”
Section: Discussionmentioning
confidence: 99%
“…a-Tocopherol attenuates the increased collagenase gene transcription in aging fibroblasts without altering the level of its natural inhibitor, tissue inhibitor of metalloproteinase through the inhibition of protein kinase C a activity [66]. A detailed study of the ROS scavenging activity of tocopherols showed that g-tocopherol is superior to a-tocopherol in its ability to scavenge NO [67]. Tocopherol, therefore, suppresses melanogenesis.…”
Section: Tocopherols (Vitamin E)mentioning
confidence: 97%